Avaliação do comportamento de sistemas estruturais de linhas de transmissão submetidos à ação do vento - Camila Cordeiro de Oliveira (2019)
This work presents an evaluation of the structural behavior of transmission lines (TL’s) subjected to non-deterministic dynamic wind loading on the cables, considering aerodynamic damping and geometric nonlinearity. The numerical methodology was developed using the software ANSYS® v. 18.2. Four different models were developed for the evaluation of the wind loads in cables of TL’s: isolated cable, coupled cables, isolated tower and the complete structural model. In dynamic analysis, wind velocity was expressed as a function of time, composed of a mean component superimposed on a fluctuant component and aerodynamic damping was determined according to the formulations proposed by Davenport (1988) and Stengel (2017). For the evaluation of the results a comparative analysis was presented between the maximum responses obtained in the dynamic (numerical) analyses with the results from equivalent static analyses according to the procedures established in codes ABNT NBR 6123: 1988, ABNT NBR 5422: 1985 and IEC 60826: 2003. The dynamic analyses performed considering the aerodynamic damping proposed by Stengel (2017) presented higher results than those obtained considering aerodynamic damping proposed by Davenport (1988). This fact occurs due to the lower values of aerodynamic damping resulting from the formulation proposed by Stengel (2017). The differences between the results of the dynamic analysis (complete model) and the equivalent static analysis (isolated tower) were significant, demonstrating the importance of performing a nonlinear dynamic analysis considering the complete structural system and suggesting the review of codes for calculation of wind forces in cables.